2015
DOI: 10.1007/s10286-015-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

The function of the autonomic nervous system during spaceflight

Abstract: Introduction Despite decades of study, a clear understanding of autonomic nervous system activity in space remains elusive. Differential interpretation of fundamental data have driven divergent theories of sympathetic activation and vasorelaxation. Methods This paper will review the available in-flight autonomic and hemodynamic data in an effort to resolve these discrepancies. The NASA NEUROLAB mission, the most comprehensive assessment of autonomic function in microgravity to date, will be highlighted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…Alteration in autonomic nervous control of venous functions with spaceflight could explain the decrease in venous resistance. Recent studies have, however, challenged the notion of reduced sympathetic activity with spaceflight suggesting that adaptations likely reflect sympathoexcitation (Verheyden et al, 2010 ; Mandsager et al, 2015 ; Norsk et al, 2015 ). Norsk et al ( 2015 ) observed that the increase in cardiac output during long duration spaceflights is more than previously observed during short duration spaceflights.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration in autonomic nervous control of venous functions with spaceflight could explain the decrease in venous resistance. Recent studies have, however, challenged the notion of reduced sympathetic activity with spaceflight suggesting that adaptations likely reflect sympathoexcitation (Verheyden et al, 2010 ; Mandsager et al, 2015 ; Norsk et al, 2015 ). Norsk et al ( 2015 ) observed that the increase in cardiac output during long duration spaceflights is more than previously observed during short duration spaceflights.…”
Section: Discussionmentioning
confidence: 99%
“…A few later studies show that the same theory might be applicable to humans 3 5 16 17 18 19 20 . However, all the studies on this phenomenon have so far focused on an activation of the otoliths 1 .…”
mentioning
confidence: 87%
“…This hypothesis necessitates clinical trials. Data obtained on integratory cardiorespiratory mechanisms might be of interest also for understanding the cardiorespiratory consequences of microgravity exposure (Migeotte et al, 2003;Prisk, 2014;Mandsager et al, 2015) and their successful surpassing by cardiorespiratory conditioning before and during the space flights.…”
Section: Discussionmentioning
confidence: 99%